Geopolitics of Water: From ‘Security’ to Sustainability - Saroch, Eva (Water Nepal, 2003)
In the context of traditional state-centric geopolitics, water disputes remain closely linked to the issue of domestic stability, political legitimacy and regime survival. The question as to ‘who gets, what, when, where and how’ is thus ideologically constructed and politically contested among various stakeholders, both within and among sovereign states. Play here is a complex kind of hydro-geopolitics, in which knowledge is not neutral but appears in various forms of the power/knowledge equation and is used by various actors in the politics of national security, identity building, ethno-religious differentiation and the exclusion of ‘others’ at various levels. Taking various examples, including some from South Asia, this paper argues that in most cases, despite the ‘green’ rhetoric of sustainability, traditional geopolitical thinking persists in the dominant approaches to the development and management of international waterways. The highly differentiated as well as fiercely contested politics and economics of water uses continue to undermine the ‘ethics of sustainability’. In order to achieve ecologically sustainable, culturally appropriate, gender sensitive and economically viable development and management of international waterways, it is important to emphasise in the first place that the specification and prioritisation of water uses is not just a scientific-technical problem area awaiting ‘expert’ intervention. What is also needed is a radical reformulation of the conventional understanding of sovereignty, security and development. Water Nepal Vol. Vol.9-10, No.1-2, 2003, pp.107-114